Tanggung Jawab Pihak Bank atas Kesalahan Sistem Komputerisasi Kartu ATM pada Bank Mandiri Ditinjau dari Ketentuan Perlindungan Nasabah - Syahrial; Maya Intan Pratiwi; Rian Prayudi Saputra (PT PUSTAKA CENDEKIA GROUP, 2024)
In serving and providing these services, banks provide computer-based facilities that are indicators, not only of progress in banking itself but also of business competition between banks that also contribute to improving the country's economy. Related to computer-based services, one of the objects is ATM facilities. ATM stands for Automatic Teller Machine or Automated Teller Machine which in Indonesia can also be interpreted as Anjungan Tunai Mandiri, is one manifestation of a computerized system that is part of banking information system technology. From the results of the study, it can be concluded that banks as institutions that work based on public trust, have a very strategic role and position in national development. The main function of banks is to collect and distribute funds to the community, so that banks are actually intermediary institutions. As a financial intermediary institution, banks become intermediaries between parties with excess funds (surplus of fouds) with parties who lack/need funds (lack of fouds). And the form of bank accountability itself is realized by resolving cases administratively and also replacing losses experienced by customers. For customers of 1 bank, they are required to replace their ATM cards with new ones so that they can be used by the person concerned. For customers 2 banks are required to compensate for losses in accordance with the losses experienced by customer 2.